2007
DOI: 10.1074/jbc.m703547200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Heterotypic Claudin Compatibility

Abstract: Tissue barrier function is directly mediated by tight junction transmembrane proteins known as claudins. Cells that form tight junctions typically express multiple claudin isoforms which suggests that heterotypic (head-to-head) binding between different claudin isoforms may play a role in regulating paracellular permeability. However, little is known about motifs that control heterotypic claudin compatibility. We found that although claudin-3 and claudin-4 were heteromerically compatible when expressed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
154
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(165 citation statements)
references
References 34 publications
(47 reference statements)
10
154
0
1
Order By: Relevance
“…37 Co-culture of HeLa cells expressing different claudin genes revealed that while CLDN1 and CLDN5 were heterotypically interacting with CLDN3, they would not heterotypically bind to CLDN4, demonstrating considerable selectivity in heterotypic claudin-claudin interactions. 38 39 FRAP studies suggest that claudin molecules assembled in tight junctions have limited mobility, 40 consistent with their known heteromeric interactions with scaffold proteins in the tight junction.…”
Section: Claudin-claudin Interactionmentioning
confidence: 85%
“…37 Co-culture of HeLa cells expressing different claudin genes revealed that while CLDN1 and CLDN5 were heterotypically interacting with CLDN3, they would not heterotypically bind to CLDN4, demonstrating considerable selectivity in heterotypic claudin-claudin interactions. 38 39 FRAP studies suggest that claudin molecules assembled in tight junctions have limited mobility, 40 consistent with their known heteromeric interactions with scaffold proteins in the tight junction.…”
Section: Claudin-claudin Interactionmentioning
confidence: 85%
“…Whether this property is important for the cldn16 selectivity filter is unknown as yet. However, the ECS2 of claudins has been described as an important determinant of trans-interaction capability (39,40). The use of claudin chimeras to identify the function of particular claudin segments involves a certain risk of misfolding.…”
Section: Discussionmentioning
confidence: 99%
“…48 Also, heterotypic claudin-claudin specificity is dictated by motifs in both the first and second EL domains. 36 Thus, a likely model is that both claudin EL domains act in concert to mediate heterotypic binding of claudins between adjacent cells.…”
Section: Discussionmentioning
confidence: 99%